The Role of Leadership Level in College Students’ Decision-Making: Evidence From Event-Related Potential Analysis - Yang, Yuwei; Du, Shunshun; He, Hui; Wang, Chengming; Shan, Xueke; Gu, Huang; Zhao, Junfeng (Frontiers in Psychology, 2021)
Although risk decision-making plays an important role in leadership practice, the distinction in behavior between human with differing levels of leadership, as well as the underlying neurocognitive mechanisms involved, remain unclear. In this study, the Ultimatum Game (UG) was utilized in concert with electroencephalograms (EEG) to investigate the temporal course of cognitive and emotional processes involved in economic decision-making between high and low leadership level college students. Behavioral results from this study found that the acceptance rates in an economic transaction, when the partner was a computer under unfair/sub unfair condition, were significantly higher than in transaction with real human partners for the low leadership group, while there was no significant difference in acceptance rates for the high leadership group. Results from event-related potentials (ERP) analysis further indicated that there was a larger P3 amplitude in the low leadership group than in the high leadership group. We concluded that the difference between high and low leadership groups was at least partly due to their different emotional management abilities.